Dynamic Analysis and Adaptive Synchronization of a New Chaotic System - Amira, Rami; Hannachi, Fareh (Journal of Applied Nonlinear Dynamics, 2026)
This research paper studies a new chaotic system modified from Lorenz system. Firstly, the stability of the fixed points are studied. then, the dynamics of the novel system are investigated using bifurcations diagrams, Lyapunov exponents, 0-1 test, as well as Poincare sections. Furthermore, we use the three previously mentioned methods and see how our system exhibit a chaotic behavior from doubling of period. In addition to that, comparison of our proposed system with 30 other systems are implemented in order to see their advantage in secure communication using Kaplan-York dimension. In the second part of this paper, we implement an identical synchronization in less than 0.4 seconds via an adaptive control law. Moreover, any results we get analytically will be checked by Matlab simulation.